Smartphone Usage Patterns and Their Physical, Psychological, and Cyber‐Behavioral Predictors Among Adolescents in South Korea. (20th May 2022) - Oh, Sumi; Park, Sunhee
ABSTRACT: BACKGROUND: Adolescents are described as digital natives, with smartphones deeply embedded in their lives. However, limited literature on smartphone usage patterns exists. This study examined adolescents' smartphone usage patterns and their physical, psychosocial, and cyber‐behavioral profiles. METHODS: We used latent profile analysis and a person‐centered approach to investigate 11 items on smartphone use purpose and use time. Participants were 2324 first‐year middle‐school students (aged 13 years) from a nationally representative dataset. RESULTS: Four distinct profile groups were observed: minimalist users, entertainment users, social users, and multifunctional users. The 4 profiles differed by gender and physical (physical activity and obesity), psychosocial (relationships with their parents, depression, and academic lethargy), and cyber‐behavioral (smartphone use time, computer use time, and cyber delinquency) status. IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: Our findings have key research and real‐world implications for developmental psychologists and school health providers, specifically for those who work with adolescents, to address concerns regarding adolescents' smartphone use. CONCLUSIONS: Adolescents use smartphones at varying times and for various purposes. A better understanding of adolescents' smartphone usage and purposes can help parents and school health providers develop and implement interventions.